Development Of Gastronomic Tourism Potential In Pontianak West Kalimantan - Febryola Indra; Juliana Juliana; Ira Hubner; Nova Bernedeta Sitorus (AGUSPATI RESEARCH INSTITUTA, 2022)
Gastronomy refers to the experience of eating from the beginning of the appetizer to the end of the dessert. One restaurant that offers gastronomic tours will usually serve 10 portions of food, from appetizers to dessert. Then each food will be told in detail the food's history, origin, and raw materials. Coupled with details such as textures, food decorations, to the way of presentation, it is hoped that they can provide a new sensation for tourists. In addition to the process of eating being a basic human need, food also provides added value in terms of enjoying the art of the food served. Pontianak has a variety of culinary delights ranging from snacks to main dishes, which have various types and pleasures. Pontianak City has various tourism potentials ranging from historical to cultural tourism, and one of them has the potential to develop culinary tourism. Pontianak has a variety of culinary delights ranging from snacks to main dishes of various types, tastes, and appearances that have their characteristics and enjoyment. This can be strong support in developing Pontianak as a Culinary City, with a statement from the Mayor of Pontianak Edi Rusdi Kamtono, who plans to build culinary centers at several points in the City of Pontianak; this is done considering the high interest in culinary lovers in the cuisine and flavors of the City. Pontianak that exists today, even culinary, is not just for eating to relieve hunger but can be tourism. Some planned points include the Sungai Jawi Parallel Road, Sungai Raya Dalam Parallel Road, and Parit Tokaya Parallel. This study uses a qualitative method, presenting the data in words, descriptions, and descriptions. In this case, the qualitative data in question is how to identify the potential for culinary and gastronomic tourism in Pontianak. The results of this study are Pontianak City has a culinary that can be developed into gastronomic tourism with efforts to link the historical and cultural values ​​of local food, follow-up activities such as tours to food-making locations and how to make food, and promotion and publication efforts. to further enhance the development of gastronomic tourism.